Implementation of Intrapreunership Education Leadership In SD IT Al-Ihsan Baleendah Bandung - Nurseha, Alamsyah; Muslihah, Neni Nadiroti; Mutaqin, Ejen Jenal; Asy’ari, Lutfi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2021)
Educational leadership is the ability to drive the implementation of education, so that educational goals can be achieved effectively and efficiently. In fostering fraternity and being responsible for making decisions, developing, and maintaining the existence of an organization, the leadership function must play a role. Competition between SDITs in Bandung Regency, especially in Baleendah District, will have an impact on how the principal should be the captain in carrying out school leadership, as has been done by SDIT Al-Ihsan Baleendah. The focus of this research is the implementation of intrapreneurship educational leadership at SDIT Al-Ihsan Baleendah. This study aims to capture the leadership implementation carried out by the principal at SDIT Al-Ihsan Baleendah. This type of research is a qualitative descriptive study. In the data collection technique, various techniques were used in this study, namely interviews, observation and documentation. The data analysis procedure used in this study was qualitative analysis. Based on the findings from the research results, it is concluded that the implementation of intrapreneurship educational leadership at SDIT Al-Ihsan Baleendah can be implemented and has a positive impact on the implementation of SDIT Al-Ihsan Baleendah.